Eight Weddings and Six Funerals: An fMRI Study on Autobiographical Memories - Benuzzi, Francesca; Ballotta, Daniela; Handjaras, Giacomo; Leo, Andrea; Papale, Paolo; Zucchelli, Michaela; Molinari, Maria Angela; Lui, Fausta; Cecchetti, Luca; Ricciardi, Emiliano; Sartori, Giuseppe; Pietrini, Pietro; et al. (Frontiers in Behavioral Neuroscience, 2018)
“Autobiographical memory” (AM) refers to remote memories from one's own life. Previous neuroimaging studies have highlighted that voluntary retrieval processes from AM involve different forms of memory and cognitive functions. Thus, a complex and widespread brain functional network has been found to support AM. The present functional magnetic resonance imaging (fMRI) study used a multivariate approach to determine whether neural activity within the AM circuit would recognize memories of real autobiographical events, and to evaluate individual differences in the recruitment of this network. Fourteen right-handed females took part in the study. During scanning, subjects were presented with sentences representing a detail of a highly emotional real event (positive or negative) and were asked to indicate whether the sentence described something that had or had not really happened to them. Group analysis showed a set of cortical areas able to discriminate the truthfulness of the recalled events: medial prefrontal cortex, posterior cingulate/retrosplenial cortex, precuneus, bilateral angular, superior frontal gyri, and early visual cortical areas. Single-subject results showed that the decoding occurred at different time points. No differences were found between recalling a positive or a negative event. Our results show that the entire AM network is engaged in monitoring the veracity of AMs. This process is not affected by the emotional valence of the experience but rather by individual differences in cognitive strategies used to retrieve AMs.